Análise do uso de recursos naturais e alternativas para aumentar a eficiência de produção em cervejarias de pequena escala: um estudo de caso - Funck, Vagner Mateus (2022)
After 2010 there was a significant increase in breweries registered by the Ministry of Agriculture, Livestock, and Supply. Most of the new registrations were from small and medium-sized breweries, which, following a market trend, seek to meet the demand for higher quality beers than commercial beers. Large breweries can achieve greater production efficiency by increasing scale. On the other hand, small and medium-sized breweries consume much more resources to produce the same amount of beer. Thus, it becomes relevant to carry out a study to understand production processes, the use of natural resources, and emissions by these companies. Given the context, the objectives of this study are to determine best practices and main opportunities to mitigate environmental impacts, increase production efficiency and reduce production costs of small and medium-sized breweries. Through a case study, an energy audit was conducted to quantify raw materials, energy, amount of beer produced, greenhouse gas emissions (GHG), and waste disposal. As a result, Key Performance Indicators (KPI) were created to compare this data with reference values from the bibliography. It was observed that the main energy losses are found in the non-reuse of the wort cooling heat and in cooking with the open pan. The most viable implementation practice is the production of beer by high gravity, which can reduce up to 10% of electrical energy consumption in the mash. To increase production efficiency, breweries must automate processes, control product losses, and increase the availability of production data by recording the history of energy and input consumption.